Multi-authority attribute-based identification scheme - Fei TANG; Jiali BAO; Yonghong HUANG; Dong HUANG; Huili WANG (Tongxin xuebao)
Based on the problem that the existing attribute-based identification scheme is all based on one single authority, which has a key escrow problem, that is, the key generation center knows all users’ private keys, an multi-authority attribute-based identification scheme was proposed.Distributed key generation technology was integrated to realize the (t,n) threshold generation mechanism of the user’s private key, which could resist collusion attacks from at most t-1 authorities.Utilizing bilinear mapping, a specific multi-authority attribute-based identification scheme was constructed.The security, computation cost and communication cost of the proposed scheme was analyzed, and it was compared with the same type of schemes.Finally, taking multi-factor identification as an example, the feasibility of the proposed scheme in the application scenario of electronic credentials was analyzed.The result shows that the proposed scheme has better comprehensive performance.